Using substantial reductant concentration with chelation therapy to enhance small aggregate dispersal, iron mobilization, and its clearance in neurodegenerative diseases - Muhoberac, Barry B. (Frontiers in Neuroscience, 2022)
Connections between altered iron homeostasis and certain neurodegenerative diseases are highlighted by numerous studies suggesting iron neurotoxicity. Iron causes aggregation in neurodegenerative disease-linked proteins as well as others and additionally facilitates oxidative damage. Iron and oxidative damage can cause cell death including by ferroptosis. As treatment for neurodegeneration, chelation therapy alone is sometimes used with modest, varying efficacy and has not in general proven to reverse or halt the damage long term. Questions often focus on optimal chelator partitioning and fine-tuning binding strength; however iron oxidation state chemistry implies a different approach. More specifically, my perspective is that applying a redox-based component to iron mobilization and handling is crucial because ferrous iron is in general a more soluble, weaker biological binder than ferric. Once cellular iron becomes oxidized to ferric, it binds tenaciously, exchanges ligands more slowly, and enhances protein aggregation, which importantly can be reversed by iron reduction. This situation escalates with age as brain reducing ability decrease, iron concentration increases, autophagic clearance decreases, and cell stress diminishes iron handling capacity. Taken together, treatment employing chelation therapy together with a strong biological reductant may effectively remove inappropriately bound cellular iron or at least inhibit accumulation. This approach would likely require high concentration ascorbate or glutathione by IV along with chelation to enhance iron mobilization and elimination, thus reducing cumulative cellular damage and perhaps restoring partial function. Potential treatment-induced oxidative damage may be attenuated by high reductant concentration, appropriate choice of chelator, and/or treatment sequence. Comprehensive study is urged.